Policy Study on Electricity Universal Service in China - World Bank (Washington, DC, 2012)
This policy study on universal access to electric power (universal service) in China is based on research conducted by the China Electricity Regulatory Commission in 2006. China's policy on universal service has three facets: First, availability, that is, power service shall be available to all users; second, non-discrimination, that is, equal treatment shall be granted to all users; and third, affordability, that is, a majority of the users can afford the service. Households across China were surveyed, with emphasis on six major metropolitan regions. A comparative study was made of the Chinese postal and telecommunications services, comparing the problems faced by them with the problems of universal access to electric power. The report also compares China's policies on universal service with those of other nations.